LUWU SOCIETYâS PERCEPTION TOWARD THE CUSTOM LAW âRIPAOPPANGI TANAâ - Musrifah, Mahfuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objective of the research was to find out the Luwu societyâs perception toward the custom law âRipaoppangi Tanaâ and its existence in the society. The method used in this research was descriptive method and the technique of data collection includes interview and document analysis. The result of the research indicates 1) the societyâs obedience toward the custom law âRipaoppangi Tanaâ because they believe that Datu was the God descent and all of their decision must be obeyed. 2) Some people are fearful of the custom law because of the sanction that will be applied to them. 3) Bravery, the society is brave to defy the custom law because the unfair sanction and it does not deserve with the violation that they do. The custom law âRipaoppangi Tanaâ in Kabupaten Luwu vanished and changed with the national law since the Independence Proclamation.